2014
DOI: 10.1007/s00421-014-2844-7
|View full text |Cite
|
Sign up to set email alerts
|

Kidney-synthesized erythropoietin is the main source for the hypoxia-induced increase in plasma erythropoietin in adult humans

Abstract: Our studies demonstrate (1) UC samples express a different glycoform distribution as compared to adult humans and hence illustrates the ability to synthesis EPO in non-kidney cells during fetal development (2) as expected hypoxia augments circulating EPO in adults and the predominant source here for remains being kidney derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…Patients with CKD had PMI values higher than those of healthy controls and rhEpo-containing samples. Patients with CKD exhibited glycosylation patterns very similar to the umbilical cord samples, which are considered to be mainly of hepatic origin 5,9 (Figure 2). Using absolute PMI values, patients with CKD presented a PMI of 36.16 11.7% that was markedly higher than that in healthy controls (9.263.8%; P,0.01) and furthermore, also higher compared with rhEpo-containing control samples (1.46 1.4%; P,0.01), whereas the CKD PMI values did not differ from the PMI values from venous umbilical cord plasma samples (53.96 10.6%; P.0.05).…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…Patients with CKD had PMI values higher than those of healthy controls and rhEpo-containing samples. Patients with CKD exhibited glycosylation patterns very similar to the umbilical cord samples, which are considered to be mainly of hepatic origin 5,9 (Figure 2). Using absolute PMI values, patients with CKD presented a PMI of 36.16 11.7% that was markedly higher than that in healthy controls (9.263.8%; P,0.01) and furthermore, also higher compared with rhEpo-containing control samples (1.46 1.4%; P,0.01), whereas the CKD PMI values did not differ from the PMI values from venous umbilical cord plasma samples (53.96 10.6%; P.0.05).…”
mentioning
confidence: 83%
“…An Epo purification kit from MAIIA Diagnostics (Uppsala, Sweden) was used to purify Epo from patient and control plasma samples and four umbilical cord plasma samples obtained from the University Hospital of Zürich. 9 The purifications were performed according to the directions by the company, which are briefly described here: 1.5-2 ml plasma was diluted in sample dilution buffer to a final volume of 20 ml and loaded to disposable anti-Epo columns with immobilized monoclonal anti-Epo antibody 3F6, which very specifically captures both endogenous and rhEpo. The Epo was eluted with 50 ml desorption buffer into Eppendorf tubes containing 5 ml adjustment buffer containing Tween 20 and BSA.…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also reported that patients with anemia can switch EPO production from the kidney to the liver [30,31], as can be shown by glycoform analysis of EPO. Indeed, the posttranslational EPO glycosylation is specific of the synthesizing cells, giving rise to different EPO glycoforms that can be used to localize EPO synthesis [30,32].…”
Section: Introductionmentioning
confidence: 99%